Maternal obesity reverses the resistance to LPS-induced adverse pregnancy outcome and increases female offspring metabolic alterations in cannabinoid receptor 1 knockout mice - Bariani, Maria Victoria (2021)
Maternal overnutrition negatively impacts the offspring's health leading to an increased risk of developing chronic diseases or metabolic syndrome in adulthood. What we eat affects the endocannabinoid system (eCS) activity, which in turn modulates lipogenesis and fatty acids utilization in hepatic, muscle, and adipose tissues. This study aimed to evaluate the transgenerational effect of maternal obesity on cannabinoid receptor 1 knock-out (CB1 KO) animals in combination with a postnatal obesogenic diet on the development of metabolic disturbances on their offspring. CB1 KO mice were fed a control diet (CD) or a high-fat diet (HFD; 33% more energy from fat) for 3 months. Offspring born to control and obese mothers were also fed with CD or HFD. We observed that pups born to an HFD-fed mother presented higher postnatal weight, lower hepatic fatty acid amide hydrolase activity, and increased blood cholesterol levels when compared to the offspring born to CD-fed mothers. When female mice born to HFD-fed CB1 KO mothers were exposed to an HFD, they gained more weight, presented elevated blood cholesterol levels, and more abdominal adipose tissue accumulation than control-fed adult offspring. The eCS is involved in several reproductive physiological processes. Interestingly, we showed that CB1 KO mice in gestational day 15 presented resistance to LPS-induced deleterious effects on pregnancy outcome, which was overcome when these mice were obese. Our results suggest that an HFD in CB1 receptor-deficient mice contributes to a “nutritional programming” of the offspring resulting in increased susceptibility to metabolic challenges both perinatally and during adulthood.